Report of the Steering Group on Employment Strategy for the Seventh Five Year Plan - Planning Commission (Planning Commission, 1984)
In the context of the preparation of the Seventh Five Year Plan 1935-90, the Planning Commission constituted a Steering Group on Employment Strategy for the Seventh Five Year Plan with Dr. C.H. Hanumantha Rao, Member, Planning Commission as Chairman vide Office Memorandum No.M-12038/26/83-LEM-EP dated 15th September, 1983 (Annexures I-IV) 1.2 The terms of reference of the Steering Group were as follows: (i) To make an overall assessment of employment/unemployment situation at the national as also at the State/regional levels including backward areas and hill/tribal areas, and separately for public and private sectors; (ii) To examine the progress of labour absorption, particularly of educated manpower and women, in the organised and un organised sectors by industry/activity classification;"
Government of India Planning Commission (Labour Employment and Manpower Division)